Radiographic progression is associated with increased cardiovascular risk in patients with axial spondyloarthritis - Kang, Kwi Young; Her, Youn Hee; Ju, Ji Hyeon; Hong, Yeon Sik; Park, Sung-Hwan (Modern rheumatology, 2016)
Objectives: To compare the cardiovascular disease (CVD) risk between axial spondyloarthritis (axSpA) patients and matched controls, and to identify factors associated with increased CVD risk in axSpA patients. Methods: This cross-sectional study enrolled 185 axSpA patients who fulfilled the Assessment for Spondyloarthritis (ASAS) criteria and 925 age- and sex-matched controls. None of the subjects had a previous history of CVD or diabetes mellitus. Traditional CVD risk factors were assessed and the 10-year CVD risk was calculated using the Framingham risk score (FRS). Estimated 10-year CVD risk was compared between axSpA patients and matched controls. Disease activity and radiographic progression in the sacroiliac joint and spine of axSpA patients were evaluated at the time of CVD risk assessment. Results: High-density lipoprotein (HDL) cholesterol levels were lower in axSpA patients than in the matched controls (p = 0.004); however, systolic blood pressure was higher (p < 0.001). The FRS was 5.0 ± 6.6% for controls and 6.3 ± 8.7% for axSpA patients (p = 0.046). Both the grade of sacroiliitis on X-ray and the number of syndesmophytes correlated with the FRS (p = 0.009 and p = 0.001, respectively), but disease activity variables did not. The FRS was significantly higher in axSpA patients with a greater number of syndesmophytes (p = 0.035). Multivariate analysis identified the number of syndesmophytes as being independently associated with the FRS (p < 0.001). Conclusions: The FRS was higher in axSpA patients than in a matched general population. Radiographic progression in the spine was associated with a high estimated 10-year CVD risk.